Why I quit zombie school - Stine, R.L. (New York, NY : Scholastic Inc., 2011)
When Matt's parents send him to a strange boarding school, where the students move at a dead-slow pace, he begins to suspect he has been enrolled in a school for zombies.
Keywords: Horror fiction; Children's stories